Optimising the Quality of Postpaid Electricity Billing Information Services through the Integration of the SERVQUAL Mixed Methods Approach - Khumaidi, Moh Naufal; Dahda, Said Salim (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
The quality of postpaid electricity billing information services is a critical factor in maintaining customer satisfaction and the operational sustainability of electricity service providers. However, the complexity of identifying service quality gaps requires an integrative and comprehensive approach. The integration of a mixed methods approach with the SERVQUAL model is considered to have the potential to optimise service quality through holistic problem identification and data-driven solutions. This study used a mixed methods design with an explanatory sequential design approach. The quantitative phase was conducted through a survey using a SERVQUAL questionnaire that measured five dimensions of service quality (tangibles, reliability, responsiveness, assurance, empathy) among 400 postpaid electricity customer respondents. Quantitative data were analysed using regression tests and gap analysis to identify discrepancies between customer expectations and perceptions. The qualitative phase was conducted through in-depth interviews with 15 customers and focus group discussions (FGD) with service staff to explore the causes of the gaps and potential solutions. Data integration was carried out through joint display analysis and triangulation. Quantitative analysis revealed negative gaps in all SERVQUAL dimensions, with the highest gaps in reliability (-1.85) and responsiveness (-1.72). The lowest gap was in tangibles (-0.95). Qualitative analysis revealed the root causes, including inaccurate billing information, slow response to complaints, and lack of empathy in communication. Data integration identified three main wastes: waiting time in delivering information, reprocessing billing data, and overburdening the information system. Improvement priorities focused on developing a real-time data integration system and training service staff. The integration of SERVQUAL mixed methods is effective in identifying service quality gaps and root causes that need to be addressed. Optimising the quality of postpaid electricity billing information services requires both a technical approach (improving the information system) and a human approach (staff training). Implementing solutions based on the findings of this study can improve customer satisfaction and operational efficiency. Further studies are recommended to test the effectiveness of the solutions in a broader context.